2009
DOI: 10.1007/s12046-009-0022-0
|View full text |Cite
|
Sign up to set email alerts
|

Development and test of a new catalytic converter for natural gas fuelled engine

Abstract: This paper presents characteristics of a new catalytic converter (catco) to be used for natural gas fuelled engine. The catco were developed based on catalyst materials consisting of metal oxides such as titanium dioxide (TiO 2 ) and cobalt oxide (CoO) with wire mesh substrate. Both of the catalyst materials (such as TiO 2 and CoO) are inexpensive in comparison with conventional catalysts (noble metals) such as palladium or platinum. In addition, the noble metals such as platinum group metals are now identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…By using a copper-based catalytic converter it was found that HC was reduced by 38% and CO by 33% at full load. Another catalytic converter was developed consisting of a TiO 2 /CoO coating over stainless steel wire mesh substrates [42]. The meshes were first coated with the metal catalysts by a washcoating technique and then arranged into a straight bar.…”
Section: Catalyst Performance Of the Stacked Wire Mesh Monoliths: Soomentioning
confidence: 99%
“…By using a copper-based catalytic converter it was found that HC was reduced by 38% and CO by 33% at full load. Another catalytic converter was developed consisting of a TiO 2 /CoO coating over stainless steel wire mesh substrates [42]. The meshes were first coated with the metal catalysts by a washcoating technique and then arranged into a straight bar.…”
Section: Catalyst Performance Of the Stacked Wire Mesh Monoliths: Soomentioning
confidence: 99%
“…According to Shahar and Majib (2007) [13], the concentration of Platinum (Pt) and Rhodium (Rh) has been taken upon road dust sample and the ratio range from the sample is in the range of 2.1 :1 to 7:1, where the ratio these elements in the catalytic converter usage is 7:1. Kalam et al, (2009) [2] has also come with new ideas in the development of catalytic converter that used the material of titanium dioxide (TiO 2 ) and cobalt oxide (CoO) as the catalyst material. The method is by using wire mesh substrate treatment immersed into a preparation of HCL solution.…”
Section: Catalyst Materialsmentioning
confidence: 99%
“…al, 2012). Kalam et al, (2009) [2] prepared the catalyst by adding 10 gm of TiO 2 with sodium silicate in order to get 10% TiO 2 slurry before continuing with homogenization process that ends with drying process to get the catalyst slurry. The Same step is used by Syed et al, (2015) [23] by adding 10 gm Al 2 O 3 with sodium silicate in order to get Al 2 O 3 nanoparticles slurry.…”
Section: Catalyst Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…It is experimentally found that the conversion efficiencies of TiO 2 /CoO-based catalytic converter are 93%, 89% and 82% for NO x , CO and HC emissions, respectively. It is calculated that the TiO 2 /CoO-based catalytic converter reduces 24%, 41% and 40% higher NO x , CO and HC emissions in comparison with OEM catco, respectively (Kalam et al 2009). Alternative vehicle (fuels and propulsion) strategies generally involve the use of alternative combustible by-products of petroleum extraction and refining (such as LPG or CNG), alcohol-based fuels, electric propulsion (either fully dedicated or as a hybrid with another fuel), or synthetically produced fuel from various types of feed stocks.…”
Section: Introductionmentioning
confidence: 99%